A Comparative Study of CO and CH Adsorption on Silicalite-1 Fabricated by Sonication and Conventional Method - Marjan Razavian; Shohreh Fatemi; Mojtaba Masoudi-Nejad (Adsorption Science & Technology)
Silicalite-1 is pure polymorph silica that is considered a member of zeolite family due to the similarity of its framework to the well-known ZSM-5. It is an organophilic and hydrophobic material with molecular sieving property that allows it to be widely used as an adsorbent. In this work, silicalite-1 is synthesized by conventional hydrothermal treatments at atmospheric (T = 80 °C) and high pressures (T = 150 °C), respectively. In addition, the procedure is repeated using ultrasound waves during the mixing and ageing steps to shorten the synthesis time. The high crystallinity and phase purity of high-temperature autoclaved and sonicated samples are confirmed by X-ray powder diffraction and scanning electron microscopy results. Moreover, adsorption equilibrium of CH 4 and CO 2 has been studied experimentally to investigate the influence of textural properties of the obtained products on their adsorption performance. The experiments were performed in a batch system on the basis of a volumetric measurement technique at various operating conditions. The sonicated silicalite-1 showed a higher CO 2 /CH 4 selectivity at lower pressures, while the autoclaved sample possessed higher adsorption capacity for both CO 2 and CH 4 . These results are explained on the basis of a difference between the inter-crystalline pore volumes, morphology and surface acidity of the fabricated adsorbents. The experimental isotherms were modelled based on the Toth equation by minimizing the mean relative difference between the model and experimental adsorption capacity.